2018
DOI: 10.5114/hm.2018.76075
|View full text |Cite
|
Sign up to set email alerts
|

Mental fatigue as a conditioner of the tactical and physical response in soccer players: a pilot study

Abstract: Purpose. the aim of the study was to verify the effect of mental fatigue on tactical actions quality and the intensity of covered distance in soccer players. Methods. Six U-15 male soccer players participated in this study (14.7 ± 0.59 years of age). For data collection, the FUtSAt and GPSports® (SPI-HPU) systems were applied. to induce mental fatigue, the Stroop task was used for 20 minutes. the individuals were evaluated in 2 conditions: mental fatigue and control (with and without the Stroop task). Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 25 publications
0
42
1
1
Order By: Relevance
“…since ssG may be used by groups with different levels -like collegiate students [30] -future studies with the formats presented here are demanded to check if the current results are applicable irrespective of the players' level of practice. Also, mental fatigue has been shown to impair players' tactical performance in ssG [31]. At this point, since the 2-floater condition may be a novel context for many players, further studies are required to verify if players mentally fatigued are able to explore the space within such a context.…”
Section: Discussionmentioning
confidence: 99%
“…since ssG may be used by groups with different levels -like collegiate students [30] -future studies with the formats presented here are demanded to check if the current results are applicable irrespective of the players' level of practice. Also, mental fatigue has been shown to impair players' tactical performance in ssG [31]. At this point, since the 2-floater condition may be a novel context for many players, further studies are required to verify if players mentally fatigued are able to explore the space within such a context.…”
Section: Discussionmentioning
confidence: 99%
“…In other two studies, no clear effects of mental fatigue were identified in small-sided games. 42,44 Coutinho et al 41 observed shorter total distances covered and Kunrath et al 43 found higher values of distance covered at speeds between 10 and 12.9 km/h and ≥ 18 km/h.…”
Section: Physical and Physiological Performancementioning
confidence: 99%
“…Four different cognitive tasks were used as a protocol for inducing mental fatigue, the AX-CPT (90 minutes), the Stroop paper [38][39][40][41] and computer version (20 -30 minutes) 42,43 , and the motor coordination task 44 . In control condition, the subjects read magazines [38][39][40] , watched TV documentaries 30,42 , and performed a warm-up lasting the same time as the intervention condition 44 .…”
Section: Cognitive Tasksmentioning
confidence: 99%
See 2 more Smart Citations